Breeding Strategies for Sustainable Forage and Turf Grass Improvement 2012
DOI: 10.1007/978-94-007-4555-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and Adaptation of Cynodon L. C. Rich Species in Australia

Abstract: Cynodon L. C. Rich comprises warm season grass species that are valuable as turf and forage in warm climates across the globe. Traditionally, Cynodon breeding programs have aimed to produce varieties with improved turf and forage grass quality characteristics. More recent goals, such as improved abiotic stress tolerance, aim to address challenges associated with climate change. Germplasm collections representing a fraction of the global distribution of Cynodon comprise the plant resource for these breeding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous bermudagrass characterization studies were limited due to the small size or limited geographic coverage of populations studied with small numbers of genetic loci sampled, leading to a limited scope in understanding the genetic structure and variations in Cynodon. For example, Wu et al (2004) surveyed the genetic diversity of 28 accessions from 11 countries while Jewell et al (2012) studied 690 accessions, all collected from Australia. The present study utilized a large worldwide germplasm collection, presumably overcoming limitations of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous bermudagrass characterization studies were limited due to the small size or limited geographic coverage of populations studied with small numbers of genetic loci sampled, leading to a limited scope in understanding the genetic structure and variations in Cynodon. For example, Wu et al (2004) surveyed the genetic diversity of 28 accessions from 11 countries while Jewell et al (2012) studied 690 accessions, all collected from Australia. The present study utilized a large worldwide germplasm collection, presumably overcoming limitations of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ploidy levels and chromosome numbers of the genus Cynodon vary widely. Flow cytometry studies revealed diploidy to hexaploidy levels in Cynodon (Wu et al, 2006;Kang et al, 2008;Gulsen et al, 2009;Jewell et al, 2012;Grossman et al, 2021). Forbes and Burton (1963) confirmed the base chromosome number as 9 in Cynodon species.…”
Section: Introductionmentioning
confidence: 96%
“…(Poaceae) is a genus of perennial plants that is typical of tropical and subtropical regions and is widely adapted to various environments. It has high morphological variability and has multiple applications in various regions worldwide, such as its use in pasture and stored forage, soil cover and sward, on golf courses, and in gardens (Wu, 2011;Jewell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%